2014
DOI: 10.1021/es5020955
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and Zinc Isotope Fractionation in Hyperaccumulating and Nonaccumulating Plants

Abstract: Until now, there has been little data on the isotope fractionation of nickel (Ni) in higher plants and how this can be affected by plant Ni and zinc (Zn) homeostasis. A hydroponic cultivation was conducted to investigate the isotope fractionation of Ni and Zn during plant uptake and translocation processes. The nonaccumulator Thlaspi arvense, the Ni hyperaccumulator Alyssum murale and the Ni and Zn hyperaccumulator Noccaea caerulescens were grown in low (2 μM) and high (50 μM) Ni and Zn solutions. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
73
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 43 publications
9
73
0
1
Order By: Relevance
“…Isotopically lighter Zn in shoots relative to roots was first reported by Weiss et al, (2005) and similar features are observed in the Ni isotopic studies of plants (Deng et al, 2014;Estrade et 795 al., 2015). In a comparison of shoot-root isotopic differences of Zn and Ni in the same species, Deng et al (2014) noted a more modest fractionations for Ni.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Isotopically lighter Zn in shoots relative to roots was first reported by Weiss et al, (2005) and similar features are observed in the Ni isotopic studies of plants (Deng et al, 2014;Estrade et 795 al., 2015). In a comparison of shoot-root isotopic differences of Zn and Ni in the same species, Deng et al (2014) noted a more modest fractionations for Ni.…”
supporting
confidence: 74%
“…It should be re-emphasised that most of the species analysed for their Ni isotopic compositions are hyperaccumulators, in which Ni is anomalously enriched shoots relative to roots. The two non-accumulators studied so far show contrasting behaviour, 800 with both positive, Thlapsi arvensa (Deng et al, 2014) and negative, Euphorbia spinosa values of Δ 60/58 Ni shoots-roots , see Figure 9. Some variability in Δ 60/58 Ni between roots, stems and leaves may be related to the growth stage of the plants .…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…High nickel phytoavailability is essential for successful Ni phytomining (Massoura et al 2004), as Ni hyperaccumulator plants take up Ni from the same soil labile Ni pools as 'normal' plants Shallari et al 2001). Nickel hyperaccumulator plants have efficient root absorption mechanisms that deplete the phytoavailable Ni pools to the extent that the soil Ni chemical equilibrium is changed (Centofanti et al 2012;Deng et al 2014). As a result, Ni from non-labile pools replenishes the labile pool over time to maintain equilibration (Centofanti et al 2012), but this is a slow process and depends on the local buffering system (Massoura et al 2004).…”
Section: Soil Ni Availability For 'Metal Crops'mentioning
confidence: 99%